PENGARUH LATIHAN DOWN THE LINE DRILL TERHADAP KELINCAHAN ATLET PUTRA BULUTANGKIS PB BANK RIAU KEPRI - Lestari E, Helzi; Slamet, Slamet; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know whether there is any influence of Down the line drill training on the athlete's spell at bulitangkis pb bank riau kepri pekanbaru. The type of research used is experimental and using one-preetest-posttest design research group. The population in this study is athletes bulutankis pb bank raiu kepri Pekanbaru which amounted to 23 people. The sample technique used is purposive sampling. Purposive Sampling is a technique of determining the sample with certain considerations .. Thus the sample in this study amounted to 6 people sample of athletes son of badminton pb bank riau kepri pekanbaru. The instrument used is the shuttle run. After that, the data were processed by statistics, to test the normality by lilifors test at a significant level of α (0.05). The hypothesis that is proposed is the influence of down the line drill exercise against agility athlete son of badminton pb bank riau kepri pekanbaru. Based on the results of the analysis, there is average pree test 13.79 and post test 13.05 there is an average increase of 0, 74 with t test that t arithmetic = 8.488> from t table = 1.943. Means t arithmetic> t table. Thus there is influence of down the line drill training against agility in athletes son of badminton Pb Bank Riau Kepri PekanbaruKeywords : Down the line drill exercise, agility, badminton